Le rôle de l'Institut des Sciences Juridiques de l'Académie Polonaise des Sciences dans la jurisprudence polonaise (Contemporary Central & East European Law, 1974)
The first part of the article is a brief review of the situation of polish jurisprudence in 1974. It is highlighted that before the Second World War the legal science had been represented by five faculties of law and not numerous group of professors and assistant professors. After the war, this modest group was reduced and had to be restored.Thanks to the evolution of socialist law in Poland, new branches of law and new scientific methods were introduced. The most popular before 1939 methods - linguistic and dogmatic were replaced by a range of  harmoniously used methods: linguistic, historic, sociologic, psychologic and comparative, as well as new technologies (cybernetics and statistics). The emphasis was put on the development of legal science in accordance with economic, social and historical sciences and psychology, philosophy and sociology. The jurisprudence is released from the French, German and Austrian influence and became a part of legal science of other socialist countries.Further part of the article is devoted to the thesis adopted in the Resolution of the Council of Ministers no 46/74 of the 8th February 1974 concerning the programme of law improvement for the period 1974-1980, in the Resolution from the VIth Congress of the Polish United Workers’ Party in 1971 and in the Resolution from the IInd Congress of Polish Science in 1973.In this broad process of changes in modern jurisprudence, it is significant to determine the role of created in 1954 Institute of Law Studies in the Polish Academy of Sciences. Its functioning is determined by the Legal Act of the 17th February 1960 about the Polish Academy of Sciences. Its seat is in Warsaw but its activity is led in the whole country. There are also two bodies out of Warsaw – the Department of Research on Legal Institutions  in Poznań and the Cabinet of Researches over the Legal Conscience in Kraków.In 1974 the Institute consisted of 15 professors, 34 assistant professors, 27 doctorate candidates and about 250 cooperating legal professionals. Publishing output was also impressive (about 15 books published each year). It is also the main institution developing the international relations. It is cooperating not only with other socialist countries but also with France, Germany, United States, United Kingdom. Cannot be underestimated the Institute’s input in legislation process and in formation of researchers in legal sciences.The Institute works accordingly to the plan adopted for years 1971-1975 which is analysed in the further part of the article, as well as its organizational structure. The prospects for the future are analysed through the plan adopted for years 1976-1980 prepared on the basis of the report “The partnership and links of the legal science” worked out by W. Czachórski.The conclusion of the article is the important role of the Institute cannot be underestimated and its activity cannot be replaced by the activity of the universities and the faculties of law and administration.